HUBUNGAN PERILAKU SEDENTARI DENGAN SINDROM METABOLIK PADA PEKERJA - Lailiyah Yusna Yusfita (Universitas Airlangga, 2018)
Sedentary lifestyle has been done by many workers either in the workplace, home, even on transportation. High sedentary lifestyle is a risk factor for metabolic syndrome among workers that cause of metabolic diseases such as Coronary Heart Disease, diabetes mellitus type 2, and Stroke. According to the International Diabetes Federation (IDF) in 2005, the metabolic syndrome is characterized by abdominal obesity plus at least 2 other positive components consisting of hypertriglycerides, low HDL cholesterol, hypertension, and hyperglycemia. This study is a cross sectional study to determine relationship of sedentary lifestyle with metabolic syndrome. 66 workers of 113 workers who performed Medical Check Up (MCU) at Prima Medika Laboratory Surabaya during November - December 2017 became a sample of this study. Sampling method was simple random sampling. The independent variables in this study were age, sex, and sedentary lifestyle. The dependent variable was metabolic syndrome. This study used Chi-square analysis to assess the relationship between independent variable and dependent variable. The results showed the prevalence of metabolic syndrome among workers was 43.9%. Of the 29 workers with metabolic syndrome, 26 workers had a sedentary lifestyle ≥ 6 hours per day with a median was 9.11 hours per day. There was a correlation between sedentary lifestyle ≥ 6 hours per day with metabolic syndrome (p = 0.000), whereas showed no association with metabolic syndrome between age (p = 0.058) and sex (p = 0.168). The conclusions of this study were sedentary ≥ 6 hours per day associated with metabolic syndrome among workers. Workers should reduce sedentary lifestyle by stretching, avoiding sitting too long while working, and increasing physical activity in the workplace.